Demanding supply management and supplying demand management: Transboundary waters in sub-Saharan Africa - Lautze, Jonathan F.; Giordano, Mark (SAGE Publications, 2007)
The emphasis of the world's transboundary water law has gradually shifted in the past half century from water resources development to water resources management and environmental protection. This change in institutional focus is a natural outcome of changing resource conditions, in particular the high levels of water resources development achieved in many regions as well as rising economic prosperity and associated changes in environmental perception. Surprisingly, this analysis reveals that transboundary water law in sub-Saharan Africa (SSA) follows these global trends even though SSA's levels of water resources development, economic prosperity, and food security are significantly lower than any other region in the world. These findings suggest that the nature of SSA's transboundary water law may be largely “handed down” from other parts of the world with different realities than those present in SSA. Recognizing this relationship can provide important lessons for improving transboundary water governance in the region.